Effect of Ultrasonic Amplitude on the Yield and Properties of Barramundi (Lates calcarifer) Skin Collagen: Effect of Ultrasonic Amplitude on the Lates calcarifer Skin Collagen - Umi Hartina Mohamad Razali; Ainaa Maisara Mohd Juraimy; Yanti Maslina Mohd Jusoh; Daniel Joe Dailin; Noorazwani Zainol; Dayang Norulfairuz Abang Zaidel; Harisun Yaâ€™akob (Journal of Tropical Life Science, 2023)
Barramundi skin, a by-product of the fish processing industry, has shown potential as an alternative collagen source. However, the commonly used acid extraction method to produce collagen rendered a low yield requires a lengthy time and is not environmentally friendly. As a result, the adoption of greener technology, such as ultrasound, to improve the conventional extraction process is emerging. This study aimed to investigate the effect of different ultrasonication amplitudes on collagen recovery from barramundi skin. The resulting collagens were evaluated for their protein, hydroxyproline and moisture content, colour, molecular weight distribution, and FTIR spectra. Ultrasound-assisted extraction (UAE) was performed at 40 (UAE40), 60 (UAE60) and 80 (UAE80) % amplitude for 20 min. For comparison, acetic acid extraction was also carried out to produce acid-soluble collagen (ASC). UAE increased the yield (p<0.05) of collagen from barramundi skin, with UAE80 exhibiting a 7-fold increment compared to ASC. Increasing the ultrasonic amplitude increased the yield considerably but decreased the hydroxyproline content, indicating a reduction in collagen quality. Furthermore, the protein content and SDS-PAGE profile of the extracted collagens revealed that UAE promoted protein degradation. FTIR spectra indicated that despite slightly varying wavenumbers, no detrimental effect on the triple helical structure was seen following UAE with the presence of amides A, B, I, II, and III. Also, the Î±1, Î±2 and ÃŸ-chains were found in all samples, although the band intensity reduced as the amplitude increased. In conclusion, given the right conditions, UAE could improve the extraction yield without influencing the collagen structure.